(3TQM efgGL GdCUhds - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, CHh SYjO CHh GdNjQ fGUQ GdOjf GdHjVGhj,J (B685 (3g` s ((3eMeO Hf eMeO Hf TQa GdTGaYi s)
(3ChdgG (B:s
(3CMeO ddg GNHQfG GdSdai aEf bdJ bO YXeJ CUhd Gdabg hgd gh EdGfHPI LeYJ ef Ydhe eJaQbI fHPg ef GdfMh hgj GdcdGe ai eYGfi GdMQha s
(3BNQgG (B:s
(3aGYde Cfg dG Edg GdG Gddg ajchf hGLHkG Ydi CeJg Hbhdg aGJHYhg hHfLGQ gPg GdeSCdI Je gPG GdTQM Je GdcJGH GdeHGQc HMeO Gddg JYGdi s
(3CJe JCdjag SfI (B752 (3g`s
(3Cced GdTQM GHf GdTGQMs
(3HgG CKGQ JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3CUhd Gdabgs